Shin Buddhism: historical, textual and interpretive studies; commemorating the twentieth anniversary of the establishment of the Numata Endowment at the Institute of Buddhist Studies, Berkeley, California - Payne, Richard K. (Institute of Buddhist Studies and Numata Center for Buddhist Translation and Research, 2007)
Pure Land systematics in India : The Buddhabhūmi-sūtra and the Trikāya Doctrin John P. Keenan -- Avadāna-vāda and the Pure Land faith Whalen Lai -- The Chan Zong in medieval China : school, lineage, or what? T. Griffith Foulk -- The transformation of the Pure Land in the development of lay Buddhist practice in China Katherine K. Velasco -- Where is the Pure Land? Controversy in Chinese Buddhism on the nature of the Pure Land Kenneth K. Tanaka -- Activity of the Aya and Hata in the domain of the sacred Bruno Lewin -- Genshin's Essentials of Pure Land rebirth and the transmission of Pure Land Buddhism to Japan Allan A. Andrews -- The conception of the Japanese kami in the Kamakura era : notes on the first chapter of the Shasekishū Hartmut O. Rotermund -- The new Buddhism of Kamakura and the doctrine of innate enlightenment Ruben L.F. Habito -- Earliest usage of "Dajing" (Daikyō) and "Wangshenglun" (ōjōron) by a non-orthodox Pure Land Buddhist : its implication for Chinese Pure Land Buddhism Kenneth K. Tanaka -- Shinzei's Discourse on practicing the Samādhi of meditating on the Buddha Richard K. Payne -- Rennyo's legacy : The letters as scripture Minor L. Rogers, Ann T. Rogers -- The brilliance of emptiness : Tanluan as a mystic of light Roger J. Corless -- Honzon : object of worship in Shin Buddhism Jōryū Chiba -- Shin Buddhist studies and secularization Mitsuya Dake -- The theme of subjectivity in Kiyozawa Manshi's Seishinshugi Gilbert L. Johnston -- Buddhist churches of America : challenges for change in the twenty-first century Tetsuden Kashima